Comprehensive Overview - Outcomes and Challenges of Bariatric Surgery - Physical, Psychological and Nutritional Considerations - Katarzyna Doman; Dawid Komada; Kamil Hermanowicz; Daria Oleksy; Agnieszka Najdek; Urszula Kaczmarska; Aleksandra Woźniak; Marcin Mycyk; Julia Nowak; Michał Jakub Cioch (Journal of Education, Health and Sport)
Obesity, defined by excessive and abnormal body fat accumulation, leads to various health conditions such as diabetes, cardiovascular diseases, and certain cancers, significantly affecting the health and increasing the risk of mortality. Bariatric surgery offers a treatment for severe obesity, with restrictive and malabsorptive methods like sleeve gastrectomy (SG), adjustable gastric banding (AGB), Roux-en-Y gastric bypass (RYGB), biliopancreatic diversion (BPD). While bariatric surgery is effective for weight loss and health improvement, it is not without complications. Postoperative challenges include surgical complications, bone loss, nutritional deficiencies and changes in metabolism. Post-bariatric surgery patients may face psychological challenges such as emotional dysregulation, eating disorders like loss of control eating or binge eating, and body image concerns related to excess skin. This article explores the various impacts of bariatric surgery, addressing both physical and psychological challenges. It emphasizes the importance of holistic patient care, considering both physical outcomes and mental health post-surgery, to ensure long-term success.